The Optimization of 12S-14P Brushless DC Motor for Drone Application: Optimization 12S-14P BLDC Motor for Drone Application - Zulkifli, Mohamad Azim Nashraf; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2021)
Brushless Direct Current (BLDC) motor drone has gained worldwide popularity. BLDC motors have become the main motor for use in all low and high-performance in electric vehicles such as drone. The problems of this motor are cogging torque undesirable aspect of some brushless direct current (BLDC) motor. The excessive torque cause motor to produce acoustic vibration such as noise, speed ripple that can cause noise and damage to the structure. This research is to design and analyse BLDC motor using JMAG software designer for drone application, to optimize torque and power density ratio of the design BLDC motor using local parameter method and to compare performances of the initial and optimization design. The method that uses is local parameter every parameter must be adjustment and must keep same volume each parameter with the initial when adjust the parameter to optimize design. To investigate the maximum torque and power that performances of the BLDC motor can be achieve. At the end of the result, analyse the torque and power initial and optimize the improvements of the motor that optimize design give better performances without any noise to the structure of the motor.